Ultra-Low-Power Indoor Light Harvesting and Solar Cell Characterization System - Darjo Ursic; Matija Pirc; Marko Jost; Marko Topic; Marko Jankovec (IEEE Access)
In this study, we present a development of a solar-powered Internet-of-Things (IoT) device, that incorporates both light energy harvesting and solar cell monitoring, which we demonstrate by long term monitoring of a single perovskite solar cell in office-like indoor environment. Using off-the-shelf components we engineered a compact, self-sufficient IoT device, with a remarkable 75% efficient energy harvesting (EH) method, at input currents in a range of microamperes. The IoT device acquires environmental data (irradiance, temperature, humidity) and solar cell electrical parameters including its IV curve, which it sends over a Bluetooth low energy (BLE) connection to a nearby access point. A single lab-scale perovskite solar cell was used to evaluate the device in a real-world office setting, over a period of one year. Our findings demonstrate that employing a perovskite solar cell with a 1 cm2 active area and a 1 F supercapacitor as a charge storage, meets the energy demands for the continuous operation of the developed IoT device at low irradiance conditions. Additionally, irradiance sensor data in combination with the full IV curve measurements of the solar cell are used to monitor the available energy and appropriately react to the environment and solar cell changes, while maintaining an extremely low average power consumption of 6 uW. At the same time, the acquired data provide a valuable information about the solar cell’s electrical behaviour, which makes the developed system an easy to use and versatile long-term monitoring device.